Cross-cultural adaptation, reliability and validity of the Fremantle Knee Awareness Questionnaire in Italian subjects with painful knee osteoarthritis - Monticone, Marco; Sconza, Cristiano; Portoghese, Igor; Nishigami, Tomohiko; Wand, Benedict M.; Sorrentino, Gregorio; Lemorini, Giulia; Respizzi, Stefano; Giordano, Andrea; Franchignoni, Franco (Health and quality of life outcomes, 2021)
Background and aim Growing attention is being given to utilising physical function measures to better understand and manage knee osteoarthritis (OA). The Fremantle Knee Awareness Questionnaire (FreKAQ), a self-reported measure of body-perception specific to the knee, has never been validated in Italian patients. The aims of this study were to culturally adapt and validate the Italian version of the FreKAQ (FreKAQ-I), to allow for its use with Italian-speaking patients with painful knee OA. Methods The FreKAQ-I was developed by means of forward–backward translation, a final review by an expert committee and a test of the pre-final version to evaluate its comprehensibility. The psychometric testing included: internal structural validity by Rasch analysis; construct validity by assessing hypotheses of FreKAQ correlations with the knee injury and osteoarthritis outcome score (KOOS), a pain intensity numerical rating scale (PI-NRS), the pain catastrophising scale (PCS), and the Hospital anxiety and depression score (HADS) (Pearson’s correlations); known-group validity by evaluating the ability of FreKAQ scores to discriminate between two groups of participants with different clinical profiles (Mann–Whitney U test); reliability by internal consistency (Cronbach’s alpha) and test–retest reliability (intraclass correlation coefficient, ICC 2.1 ); and measurement error by calculating the minimum detectable change (MDC). Results It took one month to develop a consensus-based version of the FreKAQ-I. The questionnaire was administered to 102 subjects with painful knee OA and was well accepted. Internal structural validity confirmed the substantial unidimensionality of the FreKAQ-I: variance explained was 53.3%, the unexplained variance in the first contrast showed an eigenvalue of 1.8, and no local dependence was detected. Construct validity was good as all of the hypotheses were met; correlations: KOOS (rho = 0.38–0.51), PI-NRS (rho = 0.35–0.37), PCS (rho = 0.47) and HADS (Anxiety rho = 0.36; Depression rho = 0.43). Regarding known-groups validity, FreKAQ scores were significantly different between groups of participants demonstrating high and low levels of pain intensity, pain catastrophising, anxiety, depression and the four KOOS subscales ( p ≤ 0.004). Internal consistency was acceptable (α = 0.74) and test–retest reliability was excellent (ICC = 0.92, CI 0.87–0.94). The MDC 95 was 5.22 scale points. Conclusion The FreKAQ-I is unidimensional, reliable and valid in Italian patients with painful knee OA. Its use is recommended for clinical and research purposes.